A swarm intelligence-based quality of service aware resource allocation for clouds. (6th July 2020) - Kumar, Ashok; Sharma, Anju; Kumar, Rajesh
The growing popularity of cloud computing results in very large data centres around the world with vast amount of energy requirements and CO 2 emissions. These large sized data centres demand efficient management of resources to conserve energy while satisfying quality of service (QoS) requirements of the end users. In this paper, a QoS-aware resource allocation approach using ant colony optimisation is proposed. The proposed approach is implemented in CloudSim and comprehensive performance analysis shows upto 12% energy saving.